Bifurcation Analysis for a Delayed Predator-Prey System with Stage Structure. (18th October 2010) - Jiang, Zhichao; Cheng, Guangtao
Abstract : A delayed predator-prey system with stage structure is investigated. The existence and stability of equilibria are obtained. An explicit algorithm for determining the direction of the Hopf bifurcation and the stability of the bifurcating periodic solutions is derived by using the normal form and the center manifold theory. Finally, a numerical example supporting the theoretical analysis is given.